La passió pel real i la reacció contra la metàfora en la poètica de Salvador Dalí - Santamaria de Mingo, Vicent (Caplletra. Revista Internacional de Filologia, 2006)
Between 1927 and 1937, Dalí was author of a remarkable work of poetry simultaneous to his paintings. This article attempts at analysing the theoretical corpus in which his work is based on. Dali’s ideas about poetry were always determined by the same objectivist ambition and a permanent interest in reality, in convergence with scientific research. Against the cunning arguments the painter ascribes to metaphorical processes, it will be imposed, at first, the knowledge of the outside world, thanks to Bergson and, later, the investigation of the internal world due to Freud’s sponsorship, as a result of the incorporation of Surrealism. In the last analysis, this article aims at being an innovative approach to Dali’s poetry from the theory of knowledge.